Representasi Pesan Moral Dalam Film Imperfect The Series : (Analisis Semiotika Roland Barthes) - Rovida Femila Sari, Nur; Hakim, Lukman (Meyarsa: Jurnal Ilmu Komunikasi dan Dakwah, 2023)
Discussions about films as a tool to convey messages are indispensable in public entertainment. With the development of the film world, Web series has recently become the talk of the community. One of the most popular is the series "Imperfect The Series" directed by Naya Anindita with a comedy-drama genre. The storyline is about boarding children with different personalities, regional origins and their purpose in boarding houses. Imperfect the Series. The semiotic theory of Roland Barthes is used by the author for research and the use of a qualitative descriptive approach is shown by dialogue, the behavior of the characters in one of the scenes. Based on the results of research and data analysis, it is obtained that there are two types of code mixing contained in the dialogue between characters. in the film Imperfect the series, namely the inner code mixing and outer code mixing. Friendship occurs because of the support of trust, acceptance and intimacy with each other. Acceptance is caused by good communication. Communication interpersonal is also an exchange namely the act of conveying and receiving messages reciprocally. The foundation of trust includes respecting each other and accepting differences. It is hoped that this research can serve as a reference for similar research in the future.